Correlation of the logical thinking with mastery concept of prospective biology reachers. (March 2020) - Juhanda, A; Rustaman, N Y; Hidayat, T; Wulan, A R
Abstract: This study aims to determine the description of logical thinking and mastery of concepts, analyzing the relationship between the two owned by a number of prospective biology teachers in the vertebrate zoology practice. The research method was a correlational descriptive method with a sample of one class which includes 26 prospective teachers of the Department of Biology Education, FKIP Universitas Muhammadiyah Sukabumi (UMMI), 2017/2018 semester academic year using a purposive sampling technique. Data collection was conducted using the many as 10 standard Test of Logical Thinking (ToLT) and 20 concept mastery questions. Data analysis was carried out through a correlation test. The results showed that: 1) 35% of students had logical thinking at the transition stage with an average value of 3.0; 2) 31% of students show mastery of concepts with enough categories with an average value of 63; 3) There is a moderate correlation between logical thinking and the mastery of the concept of prospective teachers with a correlation coefficient of 0.541. The understanding of the highest correlation at each indicator of logical reasoning compared to other cognitive aspects.